Witko, Andrzej: Tajemnica: A new anthology of writings on Diego Velázquez’s Las Meninas (Tajemnica «Las Meninas». Antologia tekstów) - Badach, Arthur (Boletín de Arte, 2018)
Diego Vel.zquez’s Las Meninas, painted in 1656, is not just one of the most famous European paintings dating from the Baroque period.